2005
DOI: 10.1007/s00248-003-0228-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Diversity of Nitrate Reductase Genes among Nitrate-Dissimilating Pseudomonas in the Rhizosphere of Perennial Grasses Grown in Field Conditions

Abstract: A total of 1246 Pseudomonas strains were isolated from the rhizosphere of two perennial grasses (Lolium perenne and Molinia coerulea) with different nitrogen requirements. The plants were grown in their native soil under ambient and elevated atmospheric CO 2 content (pCO 2 ) at the Swiss FACE (Free Air CO 2 Enrichment) facility. Root-, rhizosphere-, and non-rhizospheric soil-associated strains were characterized in terms of their ability to reduce nitrate during an in vitro assay and with respect to the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 61 publications
(80 reference statements)
3
20
1
Order By: Relevance
“…Hence, our study provides evidence that in soils, the numbers of proteobacteria containing periplasmic nitrate reductase are similar to the numbers of proteobacteria with the membranebound nitrate reductase. This is consistent with the results from Roussel-Delif et al (25) and Carter et al (4), which showed that a large proportion of nitrate-reducing, gram-negative isolates contain Nap. Unfortunately, it is not possible to conclude from our study whether the similar narG and napA copy numbers in many samples resulted from a majority of nitrate reducers possessing both types of nitrate reductase or from similar numbers of bacteria possessing either Nar or Nap.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Hence, our study provides evidence that in soils, the numbers of proteobacteria containing periplasmic nitrate reductase are similar to the numbers of proteobacteria with the membranebound nitrate reductase. This is consistent with the results from Roussel-Delif et al (25) and Carter et al (4), which showed that a large proportion of nitrate-reducing, gram-negative isolates contain Nap. Unfortunately, it is not possible to conclude from our study whether the similar narG and napA copy numbers in many samples resulted from a majority of nitrate reducers possessing both types of nitrate reductase or from similar numbers of bacteria possessing either Nar or Nap.…”
supporting
confidence: 93%
“…The importance and diversity of the bacteria containing Nar have been extensively studied using both cultivation-based and direct molecular approaches (3,5,7,17,19,22). However, only a few studies have focused on bacteria containing Nap (4,9,25). In this study, we investigated the relative abundances of the two types of nitrate reductases in various environments, using a real-time PCR-based assay.…”
mentioning
confidence: 99%
“…These results also suggest that the napA community was more affected by the type and amount of plant residues than the narG community. This difference between the effects of residues on the napA and narG genes can be explained by the fact that the narG and napA communities do not fully overlap, since nitrate reducers can possess either Nar, Nap, or both (47). In contrast to our results, no significant difference in denitrifier abundance between soils amended with soybean, red clover, and barley residues was observed previously by Henderson et al (21).…”
Section: Vol 76 2010 Impact Of Plant Residue Types On Nitrate Reduccontrasting
confidence: 99%
“…Two types of dissimilatory nitrate reductases, differing in location, have been characterized: a membranebound nitrate reductase (Nar) and a periplasmic nitrate reductase (Nap) (9,53). Nitrate reducers can harbor either Nar, Nap, or both (40,47). Nitrate reducers are probably the most taxonomically diverse functional community within the nitrogen cycle, with members in most bacterial phyla and also archaea (42).…”
mentioning
confidence: 99%
“…However, since potential nitrate reductase activities are expressed per gram of soil, only the gene copy numbers per gram of soil were used for further analyses of the relationships between the size, structure, and activity of the nitrate reducer community. Besides, while most nitrate reducing bacteria possess either narG or napA, a significant proportion of nitrate reducing bacteria also possess both narG and napA (39,47), which makes it difficult to convert the narG and napA gene copy numbers into nitrate reducer cell numbers. Therefore, we used the narG and napA real-time PCR data separately but also the sum of the narG and napA gene copy numbers to investigate relationships between the size, structure, and activity of the nitrate reducer community.…”
Section: Discussionmentioning
confidence: 99%